Global patterns of epipelagic gelatinous zooplankton biomass - Victoria Hobson (Marine Biology, 2011)
There is concern that overfishing may lead to a proliferation of jellyfish through a process known as fishing down the food web. However, there has been no global synthesis of patterns of gelatinous zooplankton biomass (GZB), an important first step in determining any future trends. A meta-analysis of epipelagic-GZB patterns was undertaken, encompassing 58 locations on a global scale, and spanning the years 1967–2009. Epipelagic-GZB decreased strongly with increasing total water column depth (r2=0.543, p<0.001, n=58): in shallow (<50m) coastal waters, epipelagic-GZB was typically 742x the levels in deep ocean (>2,000m) sites. However, the ratio of GZB to primary productivity showed high values across a range of depths, i.e. this measure of the relative abundance of gelatinous zooplankton did not co-vary with depth.